Odpowiedź :
xy-ab-xy+5ab=4ab
4x-5y-4y= 4x-9y
2+2ab-4= - 2+2ab
2x-5y+2x-5y= 4x-10y
2x-3y-5x-5= - 3x-3y-5
6x-6y+3x= 9x-6y
-4y-5-5x-2x= - 4y-5-7x
-2xy+3ab-5xy+3ab= - 7xy+6ab
9xy-9-9ab-9xy= - 9ab-9
4ab-3ab-3xy-3xy= ab - 6xy
Aby było lepiej masz w załączniku pokolorowane.
Pozdrowionka! ~Wika
Odpowiedź:
xy-ab-xy+5ab=4ab
4x-5y-4y= -9y+4x
2+2ab-4= -2+2ab
2x-5y+2x-5y = 4x-10y
2x-3y-5x-5= -3x-3y-5
6x-6y+3x= 9x-6y
-4y-5-5x+2x= -7x-4y-5
-2xy+3ab-5xy+3ab= -7y+6ab
9xy-9-9ab-9xy= -9ab-9
4ab-3ab-3xy-3xy= ab-6xy
Szczegółowe wyjaśnienie:
redukcja wyrazów podobnych